Effect of controlling the number of natural microorganisms on the taste and aroma of tuak (North Sumatra traditional beverage) - Hutasoit, Sumy Ester; Turnip, Nina Juliana Roberta; Agnesia, Yoli; Martgrita, Merry Meryam (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Tuak is a traditional North Sumatran beverage produced through the fermentation of nira, the quality of which is significantly affected by the microorganisms involved in fermentation. This study aimed to enhance the processing of nira into tuak through the addition of a controlled number of natural microorganisms that play an important role in the taste and aroma of tuak and to reach conclusions about the most liked tuak. A total of 10 mL of each starter with a concentration of 0.007 g/mL was added to a container containing sterile nira. Into C1 was added 10 mL of yeast starter, C2 was added 10 mL of LAB (lactic acid bacteria), and C3 was added 10 mL of consortia, with a volume ratio of AAB (acetic acid bacteria): LAB : yeast respectively 2:4:4, then fermented for 10 hours. The results of pH and %ethanol measurements for C1 were 4.29 and 5.94; C2 were 4.25 and 5.49; and C3 were 4.12 and 4.93. Organoleptic data were analyzed using the Friedman test and confirmed that the strategy affected the taste of tuak (p-value <0.05), but not the aroma. Furthermore, Wilcoxon test results clearly indicated that C2 was significantly different from C1 and C3. C2 was rated by panelists as the best in terms of taste and aroma profile, but C1 was also liked almost equally as a product (overall liked) compared to C3. The taste profile of C2 was sweet, with a slightly pungent sour aroma.